Case study research in applied linguistics - Duff, Patricia (Lawrence Erlbaum Associates, 2015)
This volume provides an overview of case study methodology and examples of published case studies in applied linguistics, without attempting to be a comprehensive survey of the innumerable case studies that exist. The case studies presented here involve teachers and learners of English and various other languages in North America and other parts of the world. Advice is also given about how to conduct and publish case studies.